PERLINDUNGAN NEGARA TERHADAP ANAK TERLANTAR (KOMPARASI HUKUM DI INDONESIA DENGAN TINJAUAN FIQH SIYASAH) - Rahmayanti; Assaad, Andi Sukmawati (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2023)
This article discusses the State Constitutional Protection Against Abandoned Children in Indonesia and Fiqh SiyasahReview. This study aims firstly to find out the general overview of neglected children in Indonesia, secondly to find out the constitutional protection of the Republic of Indonesia against neglected children and thirdly to find out the protection of Fiqhi Siyasah to neglected children. The type of research used is library research using a normative juridical approach. The data collection technique in this research is data collection by searching, reading and taking notes from the results of written works in the form of books or other sources related to the discussion. The results of this study indicate that 1. Based on KPAI data for the last 5 years starting from 2016-2020 the dominant type of child neglect cases are children with social welfare problems. experienced a decrease in the cases of neglected children. 2. To realize the social welfare of neglected children, the Government together with the Ministry of Social Affairs seeks to maintain and protect neglected children. The Ministry of Social Affairs in carrying out its duties is assisted by the Social Service located in each Regency/City. The forms of legal protection by the government for neglected children according to Law No. 35 of 2014 concerning Child Protection include: 1) Supervision, 2) Prevention, 3) Treatment, 4 ) Counseling, 5) Social rehabilitation and 6) Social assistance. 3. Based on the fiqh siyasah protection against neglected children, which refers to the siyasa dusturiyah (constitution) which is the responsibility for the protection of neglected children, a leader in this case is the government. The role of the government is very much needed in handling abandoned children in line with Islamic law because in Islamic law, whether or not a policy leader or government administrator is correct depends on the implications for the people. If the policy has implications for the benefit of the people, it is considered correct by Shari'a. impact mafsadat on the people it is considered to violate the Shari'a.